Management of cowpea flower thrips, Megalurothrips sjostedti (Thysanoptera, thripidae), in Cameroon - Ngakou, A.; Tamò, Manuele; Parh, I.A.; Nwaga, D.; Ntonifor, N.N.; Korie, S.; Nebane, C.L.N. (Elsevier, 2008)
A series of experiments were conducted in Cameroon to investigate options for managing cowpea flower thrips, Megalurothrips sjostedti, via arbuscular mycorrhiza fungi, rhizobia and Metarhizium anisopliae. Six cowpea fields were established in three agroecological zones over a 3-year period. The abundance of both larvae and adults of M. sjostedti was assessed on plants grown from (1) seeds co-inoculated at sowing with arbuscular mycorrhiza fungi (AMF) and rhizobia (mycorrhiza/rhizobia); (2) non-inoculated seeds and plants sprayed three times with M. anisopliae (Metarhizium); (3) seeds co-inoculated at sowing with AMF and rhizobia and plants sprayed three times with M. anisopliae (mycorrhiza/rhizobia/Metarhizium); (4) non-inoculated seeds and plants sprayed three times with the synthetic insecticide deltamethrin; and compared with (5) a control consisting of non-inoculated seeds and unsprayed plants. Results indicate that thrips infestation was associated with the flowering cycle and was higher in the first than in the second cropping season in most agroecological zones. In general, M. sjostedti larval and adult counts were significantly higher (Po0.01) in the control than in other treatments. Compared with the control, treatment insecticide obtained the highest reduction of adults (range 52–95%) and larvae thrips population (64–97%), followed by mycorrhiza/rhizobia/Metarhizium (29–56%) and (29–49%), mycorrhiza/rhizobia (31–49%) and (24–52%), and Metarhizium (25–58%) and (5–52%), respectively. In all of the above treatments, the reduction of thrips led to a subsequent increase of seed yield, although it was not always significant. Apart from two cases (Ngaounde´re´ 2000 and Nkolbisson 1999), biological treatments (Metarhizium, mycorrhiza/rhizobia and mycorrhiza/rhizobia/Metarhizium) consistently reduced grain yield loss in the trials compared with the control at Ngaounde´re´ in 1999 and Maroua 2001. These results are discussed in the context of sustainable management of M. sjostedti populations on cowpea. r 2007 Elsevier Ltd. All rights reserved.